RANCANG BANGUN SISTEM KUNCI MOBIL DAN MONITORING MENGGUNAKAN ESP8266 - Phalah, Surya Mahendra; Wisaksono, Arief; Saputra, Dwi Hadidjaja Rasjid; Falah, Agus Hayatal (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Optimal vehicle security is an important aspect in preventing theft and protecting vehicles. This research focuses on designing and developing an ESP8266-based car lock and monitoring system that can be controlled wirelessly. This system allows users to lock and unlock cars and monitor vehicle conditions through a mobile application or web interface. The ESP8266 module acts as the main controller connected to sensors to detect changes in key status and vehicle conditions. In addition, the system is designed to send real-time notifications to users if suspicious activity is detected. The test results show that this system can operate stably and responsively, thus providing an effective and accessible security solution for vehicle owners.